Optimal row configuration in jujube-cotton intercropping systems increases cotton yield by enhancing growth characteristics and photosynthetically active radiation in arid region - Wang, Jinbin; Wang, Peijuan; Li, Xiaofei; Cui, Zhengjun; Li, Ling; Hu, Qiang; Qiao, Hang; Zhang, Wei; Wan, Sumei; Chen, Guodong (Frontiers in Plant Science, 2025)
BackgroundIn southern Xinjiang, intercropping cotton with jujube trees improves resource use efficiency and boosts farmers' economic benefits compared to monoculture jujube systems. However, the optimal row configuration for cotton in jujube-cotton intercropping systems remain unclear. MethodsThis study investigated the effects of cotton row configurations [2 rows (IC2), 4 rows (IC4), and 6 rows (IC6)] on cotton growth characteristics, photosynthetically active radiation (PAR), yield, and land equivalent ratio (LER) in jujube-cotton intercropping systems.ResultsThe leaf area index (LAI) and leaf area duration (LAD) followed the order of IC6 > IC4 > IC2. The intercepted PAR was improved with the increasing rows of cotton, while the transmitted PAR showed a decreasing trend. Dry matter accumulation (DMA) under IC2 and IC4 decreased by approximately 71% and 36% respectively, compared to IC6. While DMA under IC2 was 54.9% lower than that under IC4. Cotton yield under IC6 increased by approximately 98% and 31% compared to IC2 and IC4, respectively, which demonstrated a 51% significant improvement under IC4 compared to IC2. IC4 and IC6 exhibited a higher LER than IC2. However, the jujube yield under IC6 was lower compared to IC2 and IC4. The total yield under IC4 was higher than that under IC2 and IC6. As the number of cotton rows increased, the rate of improvement in cotton growth characteristics demonstrated a diminishing trend. Cotton yield was significantly correlated with LAI, PAR, and DMA. PAR showed significant relationships with LAI and DMA.ConclusionTaken together, four rows' cotton planted between jujube trees is recommended for achieve high crop production in the jujube-cotton intercropping system of South Xinjiang region.